Competitivita’ internazionale e capacita’dinamiche: il caso delle piccole e medie torrefazioni italiane - Pascucci, Federica (Piccola Impresa / Small Business, 2016)
The determinants of firms export performance represent a "big question" in International Business Studies. The purpose of this paper is to provide a solution to this question by analyzing the international competitive performance of small and medium Italian roasting companies and its determinants. The coffee industry has been changed for several years. Despite the increase in international demand and the fact that coffee is one of the Made in Italy symbols, Italian companies are now losing market share in foreign markets . The empirical analysis of six case studies highlighted the critical issues linked to the international business presence and ultimately showed that the loss of competitiveness is due mainly to the lack of "dynamic marketing capabilities", which has effectively prevented the firms to innovate and renewal their value proposition.